Analysis of highly radiative scenarios for the EU‐DEMO divertor target protection. Issue 6 (6th June 2018) - Subba, F.; Coster, D.P.; Escat Juanes, A.N.; Fable, E.; Wenninger, R.; Zanino, R.
Abstract : We employ the SOLPS5.1 code to analyse different impurity choices and injection methods as possible drivers for highly radiative scenarios in the European DEMO (EU‐DEMO). We aim at assessing the existence of a suitable parameter region to safely operate the divertor in H‐mode discharges. It turns out that such an operational region exists, and that puffing is strongly preferred to pellet as the impurity injection method. It also appears that many different impurity mixtures can meet the divertor survival requirements, with a low level of W sputtering. This provides an additional degree of freedom, which will be exploited in the future to optimize the overall reactor performance.